Music Ensemble Learning in Extra-Curricular Activities by Using Counting Methods (Universitas Negeri Semarang, 2019)
The objectives of the study is to explain the functions of counting methods used in music ensemble lessons as extracurricular activities in an elementary school. This study applied a qualitative approach. This study took place in SDN 4 (Public Elementary School 4) Godong, Grobogan, Central Java. The data of study was collected using observations, interviews, and documentation techniques. The data of the study was validated using triangulation points of resource and technique. The data was analyzed using data collection, reduction, presentation and conclusion techniques. The result of the study shows that counting method is a method that a teacher can use to make ensemble music easier for pupils to learn. In this method, the teacher uses counting symbols to make it easier for pupils to learn the materials. The steps used are determining songs, which will be played to know the bars of the song, to write the counting and the symbols, to explain the meaning of each symbol, and to play the instruments while counting individually or in a band. The evaluation of ensemble music learning was taken in a simple performance of the pupils. The evaluation of the music ensemble learning using counting method shows that pupils master the material, music instrument playing technique, as well as positive attitudes show by them.